Molecular mechanisms of MYCN-dependent apoptosis and the MDM2–p53 pathway: an Achille’s heel to be exploited for the therapy of MYCN-amplified neuroblastoma - Petroni, Marialaura; Veschi, Veronica; Gulino, Alberto; Giannini, Giuseppe (Frontiers in Oncology, 2012)
The p53 oncosuppressor is very seldom mutated in neuroblastoma, but several mechanisms cooperate to its functional inactivation in this tumor. Increased MDM2 levels, due to genetic amplification or constitutive inhibition of p14ARF, significantly contribute to this event highlighting p53 reactivation as an attractive perspective for neuroblastoma treatment. In addition to its role in tumorigenesis, MYCN sensitizes untransformed and cancer cells to apoptosis. This is associated to a fine modulation of the MDM2-p53 pathway. Indeed MYCN induces p53 and MDM2 transcription, and, by evoking a DNA damage response (DDR), it stabilizes p53 and its proapoptotic kinase HIPK2. Through the regulation of the HIPK2-p53 inhibitor HMGA1 and the homeobox proteins BMI-1 and TWIST-1, MYCN establishes a delicate balance between pro- and anti-apoptotic molecules that might be easily perturbed by a variety of insults, leading to cell death. MDM2-p53 antagonists, such as Nutlin-3, are strikingly prone to inducing death in MYCN-amplified neuroblastoma, by further pushing on HIPK2 accumulation. Here we discuss implications and caveats of exploiting this pathway and its connections to MYCN-induced DDR for a tailored therapy of MYCN-amplified neuroblastoma.